Influence of microwave assisted freezing parameters on ice crystal growth - Gustinelli, Graziele; Andreu-Cabedo, Patricia; Lopez-Quiroga, Estefania; Xanthakis, Epameinondas (My University, 2020)
Final quality of frozen foods is determined by the shape and size of the formed ice crystals, as they might cause irreversible damage to the cellular structure –crystals larger than cells will break them appart, impairing quality. Recent studies using microwave assisted freezing (MAF) – a novel alternative freezing technology – have shown that microwave radiation can influence the ice crystal formation leading to crystal size reduction. Two concepts have been proposed regarding the mechanism of action such as ”NITOM” concept (Nucleation Induced by Temperature Oscillation caused by MWs) and the ”NIMIW” (Nucleation Induced by constant or pulsed MIcroWaves power). The present study aimed to enlighten the influence of different microwave assisted freezing parameters on the ice crystal growth. A Response Surface Method (RSM) has been used to evaluate the effect of three process parameters (i.e. MW pulse width, power and cooling rate) on final crystal size, correlating processing conditions to final crystal sizes and setting the basis for further analysis.
Keywords: Freezing; Electromagnetism; Expérimentation; Food; Crystal; Crystallization; Wave